Modelling the distribution of multidimensional poverty scores: Evidence from Mexico - Berenger, Valérie; Calderón Villarreal, Cuauhtémoc; Celestini, Franck (Estudios Económicos de El Colegio de México, 2009)
The main purpose of this paper is to explore a new methodology already developed by Berenger and Celestini (2006). This theoretical method based on fuzzy sets approach makes it possible to define a multidimensional poverty score lying, as for income, between 0 and in- finity in order to characterize the organization of poverty. This method is applied using the data from the XII Census of Mexico, 2000 (INEGI). The results obtained enable us to build a typology of poverty. And we derive public policy implications.